Palladium nanoparticle effects on endocrine reproductive system of female rats. (October 2018) - Leso, V; Fontana, L; Marinaccio, A; Leopold, K; Fanali, C; Lucchetti, D; Sgambato, A; Iavicoli, I
The widespread industrial application of nanomaterials (NMs) has dramatically increased the likelihood of environmental and occupational exposure of humans to such xenobiotics. This issue, together with the increasing public health interest in understanding the effects of chemicals on endocrine system, encouraged to investigate the disruptive potential of NMs on the endocrine function. Therefore, the aim of this study was to evaluate the effects of palladium nanoparticles (Pd-NPs) on the female reproductive system of Wistar rats, intravenously exposed to different doses (0.12, 1.2, and 12 µg/kg), through the assessment of possible quantitative changes in the serum concentrations of several sex hormones. Our results demonstrated that the highest exposure doses significantly reduced the estradiol and testosterone concentrations, while increased the luteinizing hormone levels in treated animals compared to controls. Such alterations are indicative for an abnormal reproductive axis function. However, further investigations are needed to clarify the role of the different NP physicochemical properties in determining such effects, and possible underlining molecular mechanisms, as well as their relevance for the development of diseases in the female reproductive system. Overall, this may be helpful to define accurate risk assessment and management strategies to protect the health of the general and occupational populations exposed to Pd-NPs.